2008
DOI: 10.2174/1874357900802010044
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of ESTs from a Chaetognath Reveals a Deep-Branching Clade of Retrovirus-Like Retrotransposons

Abstract: Chaetognaths constitute a small marine phylum exhibiting several characteristic which are highly unusual in animal genomes, including two classes of both rRNA and protein ribosomal genes. As in this phylum presence of retrovirus-like elements has never been documented, analysis of a published expressed sequence tag (EST) collection of the chaetognath Spadella cephaloptera has been made. Twelve sequences representing transcript sections of reverse transcriptase domain of active retrotransposons were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Moreover, in their S. cephaloptera EST collection, Marletaz et al [ 9 ] have found that some sequences are similar to those of reverse transcriptase genes or of parts of retrotransposons; similarly, LINE-like and Gypsy -like retrotransposons have been found in Sagitta sp . [ 57 ] and in S. cephaloptera [ 58 ], showing evidence of the presence of functional reverse transcriptase proteins in chaetognath cells. Interestingly, SINE elements are retrosequences; this group contains all the sequences arisen by reverse transcription of ribosomal, messenger and small stable RNAs [ 59 , 60 ].…”
Section: Responsementioning
confidence: 99%
“…Moreover, in their S. cephaloptera EST collection, Marletaz et al [ 9 ] have found that some sequences are similar to those of reverse transcriptase genes or of parts of retrotransposons; similarly, LINE-like and Gypsy -like retrotransposons have been found in Sagitta sp . [ 57 ] and in S. cephaloptera [ 58 ], showing evidence of the presence of functional reverse transcriptase proteins in chaetognath cells. Interestingly, SINE elements are retrosequences; this group contains all the sequences arisen by reverse transcription of ribosomal, messenger and small stable RNAs [ 59 , 60 ].…”
Section: Responsementioning
confidence: 99%